WEAGov implementation manual - Kyle, Jordan; Ragasa, Catherine (International Food Policy Research Institute, 2024)
The Women’s Empowerment in Agrifood Governance (WEAGov) is an assessment tool developed by the International Food Policy Research Institute (IFPRI) and partners to evaluate women’s empowerment across the national policy cycle related to agrifood systems. WEAGov helps national policymakers, civil society actors, and researchers identify specific gaps and opportunities for enhancing women’s voice and agency in the agrifood policy process. It also aids in monitoring progress towards women’s empowerment in agrifood systems governance and related Sustainable Development Goals (SDGs). This implementation manual describes WEAGov’s approach and methodology and provides guidance for its use. Additional support materials are available on the WEAGov project website (https://www.ifpri.org/project/womens-empowerment-agrifood-governance-weagov/), which is regularly updated.